Research on Measurement Methods of Friction Coefficient. Issue 1 (1st February 2022) - Cao, Hongjun; Xu, Zijian; Hu, Yinjie; Zhong, Minjia; Liu, Sheng
Abstract: The concept and classification of the friction coefficient are introduced by the slope method and the plane method. In general, the development trend of friction coefficient measurement methods can be summarized as three characteristics: from simple to complex, from rough to precision, and from single function to platform integration. It also suggests the direction of friction coefficient measurement.